An improvised low cost hardening protocol for in vitro raised plantlets of Gerbera jamesonii - NAZKI, IMTIYAZ T; SIDDIQUE, M A A; RATHER, Z A; MIR, M A; BHAT, M A (The Indian Journal of Agricultural Sciences, 2015)
The present investigation comprised two experiments comparing media and containers for optimization of hardening protocol of in vitro raised plantlets of Gerbera jamesonii Bolus. cultivars Rejiko and South Pacific. In one experiment six different media formulations, viz. cocopeat, cocopeat + perlite (1:1), cocopeat + perlite + vermiculite (1:1:1), perlite, perlite + vermiculite (1:1) and vermiculite were tried in six replication completely randomized design. Days to establishment (13.60 and 12.97 in cultivars Rejiko and South Pacific respectively) was significantly lower in in vitro raised plantlets hardened in perlite + vermiculite (1:1) media formulation. Hundred percent (100%) survival of in vitro raised plantlets was achieved in the same media. In the second experiment traditional 500 ml wide mouthed glass bottle was compared with an improvised module devised out of two 250 ml polypropylene glasses-one inverted over the other and joint sealed with a strip of para film. Mean survival rate of 90% in vitro raised plantlets was achieved in polypropylene hardening module as against 70 % in glass bottle containers. Field survival of polypropylene module hardened gerbera plants after 4 and 8 weeks was significantly higher (above 95%) compared to around 70% in plants previously hardened in glass bottles. Vegetative growth in terms of leaf area and leaf number/plant was significantly higher in plants derived from polypropylene hardening modules. The hardening module developed in our study is low cost and can be employed in a variety of crops in low budget tissue culture units that cannot afford expensive hardening facilities.